2018
DOI: 10.1103/physrevlett.120.086802
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Nematic Orders of the Two-Dimensional Electron Gas at Oxide (111) Surfaces and Interfaces

Abstract: Recent experiments have explored two-dimensional electron gases (2DEGs) at oxide (111) surfaces and interfaces, finding evidence for hexagonal symmetry breaking in SrTiO_{3} at low temperature. We discuss many-body instabilities of such (111) 2DEGs, incorporating multiorbital interactions in the t_{2g} manifold which can induce diverse magnetic and orbital orders. Such broken symmetries may partly account for the observed nematicity, cooperating or competing with phonon mechanisms. We present an effective fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…This configuration has been likened to a strongly correlated analogue of graphene, and has been predicted to exhibit topological properties, unconventional superconductivity, as well as nematic phases. [14][15][16] Electric transport measurements have shown that the (111) LAO/STO interface exhibits many of the properties already seen in (001) LAO/STO, including a coexistence of superconductivity and magnetism. [17][18][19][20] However, the feature that distinguishes the (111) interface from the (001) interface is the strong anisotropy with respect to surface crystal direc-arXiv:1708.04809v2 [cond-mat.str-el] 28 Aug 2017 tion seen in almost all properties, including conductivity, Hall effect, superconductivity, quantum capacitance and longitudinal magnetoresistance.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This configuration has been likened to a strongly correlated analogue of graphene, and has been predicted to exhibit topological properties, unconventional superconductivity, as well as nematic phases. [14][15][16] Electric transport measurements have shown that the (111) LAO/STO interface exhibits many of the properties already seen in (001) LAO/STO, including a coexistence of superconductivity and magnetism. [17][18][19][20] However, the feature that distinguishes the (111) interface from the (001) interface is the strong anisotropy with respect to surface crystal direc-arXiv:1708.04809v2 [cond-mat.str-el] 28 Aug 2017 tion seen in almost all properties, including conductivity, Hall effect, superconductivity, quantum capacitance and longitudinal magnetoresistance.…”
mentioning
confidence: 98%
“…This configuration has been likened to a strongly correlated analogue of graphene, and has been predicted to exhibit topological properties, unconventional superconductivity, as well as nematic phases. [14][15][16] Electric transport measurements have shown that the (111) LAO/STO interface exhibits many of the properties already seen in (001) LAO/STO, including a coexistence of superconductivity R⊡ (kΩ) 0 5 10 15 20 Vg (V) 40 50 60 70 80 90 100 [112] [110] Ti 1 Ti 2 Ti3 O [110] [112] [ 1 1 1 ] [110] (a) (b) I VL VH VL VH [112] [110] I T=4.4K [112] FIG. 1. a) Schematic representation of the first three monolayers at the LAO/STO interface with the [112] and [110] labeled.…”
mentioning
confidence: 99%
“…The crystal symmetry of the (111) oriented LAO/STO interface at room temperature is C 3 . 14,15 This hexagonal symmetry has led to predictions of novel properties in the normal and superconducting properties of the 2D conducting gas (2DCG) at the (111) LAO/STO interface. [14][15][16] In particular, Boudjada et al 14 have predicted emergent magnetic and in-plane nematic order in the normal state resulting from broken rotational symmetry at the interface, driven in part by multi-orbital and spin-orbit interactions.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 This hexagonal symmetry has led to predictions of novel properties in the normal and superconducting properties of the 2D conducting gas (2DCG) at the (111) LAO/STO interface. [14][15][16] In particular, Boudjada et al 14 have predicted emergent magnetic and in-plane nematic order in the normal state resulting from broken rotational symmetry at the interface, driven in part by multi-orbital and spin-orbit interactions. The electronic nematicity in the normal state manifests itself as an anisotropy with respect to crystal surface direction that is observed in almost all the electronic properties of the (111) interface, including the longitudinal resistance, Hall effect and quantum capacitance.…”
Section: Introductionmentioning
confidence: 99%
“…(3) with significant nesting, which could lead to charge or spin density instabilities, and possibly to the recently predicted nematic phases. 31…”
mentioning
confidence: 99%